Comprehensive Analysis of Clinical Trials Registration for Lupus Nephritis Therapy on ClinicalTrials.gov - Gao, Yanfang; Wang, Yuhan; Li, Rongshan; Zhou, Xiaoshuang (Frontiers in Medicine, 2021)
Objective: Clinical trials are the most effective method for evaluating therapeutic strategies. The purpose of this study was to comprehensively assess the characteristics of trials on lupus nephritis (LN) and provide a reference for LN treatment and research. Methods: Registered therapeutic trials on drug interventions for LN were obtained from ClinicalTrials.gov up to December 3, 2020. The general characteristics, methodological characteristics, detailed characteristics, investigated drugs, eligibility criteria, and outcome measures of these trials were analyzed. Results: A total of 126 eligible trials were evaluated, and these trials mainly investigated the initial treatment of adult proliferative LN. Half of the trials enrolled <50 participants, and 70.7% of the trials lasted for 6–24 months. In total, 95.2% of trials adopted an interventional study design. Of intervention trials, 56.6% were in phase 2 or phase 3, 76.7% were randomized, 77.5% employed a parallel assignment, and 41.7% were masked. The eligibility criteria and outcome measures of the included trials varied and involved a variety of indicators. Chemical agents and biologics are the most widely studied immunotherapies, of which mycophenolate mofetil, tacrolimus, and rituximab are the most studied. In addition, some trials studied cell transplantation treatment. Conclusions: The majority of clinical trials for LN therapy registered on ClinicalTrials.gov investigated the initial treatment of adult proliferative LN, and most of these trials were randomized, parallel assigned, and insufficiently masked interventional trials with small scale, short duration, various eligibility criteria, and outcome measures. We hope that more large-scale, long-term multicenter, and high-quality RCT trials with standardized inclusion criteria/exclusion criteria and treatment effect evaluation systems will be conducted and that more energy and funding will be put into exploring biological products and stem cell therapies. In addition, trials for membranous LN, childhood-onset LN, and maintenance phase LN are needed to establish optimal treatment strategies.